The physiologic and physiopathologic roles of perivascular adipose tissue and its interactions with blood vessels and the renin-angiotensin system. (November 2021) - Balakumar, Pitchai; Alqahtani, Ali; Khan, Noohu Abdulla; Alqahtani, Taha; A, Thangathirupathi; Jagadeesh, Gowraganahalli
Abstract: The perivascular adipose tissue (PVAT) refers to an ectopic local deposit of connective tissue that anatomically surrounds most of the blood vessels. While it was initially known only as a structural support for vasculature, the landmark findings of Soltis and Cassis (1991), first demonstrating that PVAT reduces the contractions of norepinephrine in the isolated rat aorta, brought the potential vascular role of PVAT into the limelight. This seminal work implied the potential ability of PVAT to influence vascular responsiveness. Several vasoactive/vasocrine substances influencing vascular homeostasis were successively shown to be released from PVAT that include both adipocyte-derived relaxing and contracting factors. The PVAT is currently recognized as a metabolically active endocrine organ and is eventually considered as the ' protagonist ' in vascular homeostasis. It plays prominent defending and opposing roles in vascular function, while the actual vascular influences of PVAT vary with an increase in adiposity. Recent studies have presented compelling evidence implicating the pivotal role of PVAT in the local activation of the renin-angiotensin system (RAS), which substantially impacts vascular physiology and physiopathology. Current findings have advanced our understanding of the role of PVAT in favorably or adversely modulating the vascular function through differential RAS activation. Given that adipocytes also produce major RAS components locally to influence vascular function, this review provides a scientific basis to distinctly understand the key role of PVAT in regulating the autocrine and paracrine functions of vascular RAS components and its potential as an emerging therapeutic target for mitigating cardiovascular complications. Graphical Abstract: ga1